Pengaruh Aksi Boikot terhadap Perubahan Harga Saham, Trading Volume, dan Penjualan pada Perusahaan Berafiliasi dengan Israel yang Terdaftar di BEI - Sri Natalia Maharani Br Sinulingga; Usep Syaipudin (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
This study examines the impact of boycott actions on changes in company performance, including stock prices, trading volume, and sales, among Israel-affiliated companies listed on the Indonesia Stock Exchange (IDX) in 2023. Using an event study method with a 60-day observation window (H-30 to H+30), the research found a significant decrease in stock price, changes in trading activity, and varying effects on sales. The findings indicate that boycotts, as social movements, can influence market sentiment and investor decisions, especially under the backdrop of global political conflicts.